2018
DOI: 10.1177/0022185618766679
|View full text |Cite
|
Sign up to set email alerts
|

Australian industrial relations in 2017

Abstract: This article introduces the Journal of Industrial Relations Annual Review of Industrial Relations in 2017. It discusses the Fair Work Commission's decision to reduce Sunday and public holiday penalty rates for workers in the retail and hospitality industries, the growing problem of low wages, and the Turnbull government's policy changes relating to the employment of temporary migrant workers. It then provides an overview of the other articles contained in the Annual Review issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This, in combination with the electoral damage caused by WorkChoices in 2010, explains why the Coalition has been largely unsuccessful in attempts to alter the Fair Work framework since its reelection in 2013. The main changes instituted have not been gamechanging in any sense (Wright 2018;Clibborn 2019), especially when viewed from the perspective of minimum labour standards. A partial exception, which indeed is beneficial rather than detrimental to social protection, is the Fair Work Amendment (Protecting Vulnerable Workers Act) of 2017, which extended employer liability provisions imposed upon franchisors and holding companies in cases of wage theft.…”
Section: Momentary Change Amid Continuity In Employment Relationsmentioning
confidence: 99%
“…This, in combination with the electoral damage caused by WorkChoices in 2010, explains why the Coalition has been largely unsuccessful in attempts to alter the Fair Work framework since its reelection in 2013. The main changes instituted have not been gamechanging in any sense (Wright 2018;Clibborn 2019), especially when viewed from the perspective of minimum labour standards. A partial exception, which indeed is beneficial rather than detrimental to social protection, is the Fair Work Amendment (Protecting Vulnerable Workers Act) of 2017, which extended employer liability provisions imposed upon franchisors and holding companies in cases of wage theft.…”
Section: Momentary Change Amid Continuity In Employment Relationsmentioning
confidence: 99%
“…There appears to be some consensus on the need for reform, but a gulf remains as to why change is needed and what form it should take. The union movement's 'Change the Rules' campaign, which commenced in 2017 (Wright, 2018), continued to press for major reform to address continuing stagnant wage growth by allowing industry bargaining and the right to strike to support it (Bray et al, 2019). The Shadow Minister for Employment and Workplace Relations indicated that, should Labor form government after the 2019 election, it might be open to industry-wide bargaining (McCauley, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, over this period, constant change has been a characteristic of Australian industrial relations policy, including departure from the longstanding system of conciliation and arbitration in favour of decentralised bargaining. Australia's various reforms have been motivated by numerous factors, including party politics (Wright, 2018) and neoliberal ideology (Cooper and Ellem, 2008), and following the pendulum swinging on the continuum between equity and flexibility (Befort and Budd, 2009;Buchanan and Callus, 1993;Wright, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation